Rhinovirus-induced interferon production is not deficient in well controlled asthma. Issue 3 (14th October 2013) - Sykes, Annemarie; Macintyre, Jonathan; Edwards, Michael R; del Rosario, Ajerico; Haas, Jennifer; Gielen, Vera; Kon, Onn Min; McHale, Mark; Johnston, Sebastian L
Abstract : Background: Defective rhinovirus (RV)-induced interferon (IFN)-β and IFN-λ production and increased RV replication have been reported in primary human bronchial epithelial cells (HBECs) from subjects with asthma. How universal this defect is in asthma is unknown. Additionally, the IFN subtypes induced by RV infection in primary HBECs have not been comprehensively investigated. Objective: To study RV induction of IFN-α, IFN-β and IFN-λ and RV replication in HBECs from subjects with atopic asthma and healthy controls. Methods: HBECs were obtained from subjects with asthma and healthy controls and infected with RV16 and RV1B, and cells and supernatants harvested at 8, 24 and 48h. IFN proteins were analysed by ELISA and IFN mRNA and viral RNA expression by quantitative PCR. Virus release was assessed in cell supernatants. Results: IFN-β and IFN-λ were the only IFNs induced by RV in HBECs and IFN-λ protein induction was substantially greater than IFN-β. Induction of IFN-λ1 mRNA by RV16 at 48h was significantly greater in HBECs from subjects with asthma; otherwise there were no significant differences between subjects with asthma and controls in RV replication, or in induction of type I or III IFN protein or mRNA. Conclusions: IFN-λ and, to a lesser degree, IFN-β are the major IFN subtypes induced by RV infection of HBECs. Neither defective IFN induction by RV nor increased RV replication was observed in the HBECs from subjects with well controlled asthma reported in this study.